2015
DOI: 10.1007/s10956-014-9545-1
|View full text |Cite
|
Sign up to set email alerts
|

Understanding Co-development of Conceptual and Epistemic Understanding through Modeling Practices with Mobile Internet

Abstract: The present study explores how engaging in modeling practice, along with argumentation, leverages students' epistemic and conceptual understanding in an afterschool science/math class of 16 tenth graders. The study also explores how students used mobile Internet phones (smart phones) productively to support modeling practices. As the modeling practices became more challenging, student discussion occurred more often, from what to model to providing explanations for the phenomenon. Students came to argue about e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…A few studies have examined the use of mobile technology in science education and its impact on student learning. Ryu, Han, and Paik () found that smartphones, as supplemental resources to scientific modelling activities, facilitated student collaboration and deepened conceptual discussion. In a quasi‐experiment by Hwang, Wu, and Ke (), elementary school students used interactive concept maps on mobile devices in natural science courses that improved their attitudes towards and achievements in science learning.…”
Section: Introductionmentioning
confidence: 99%
“…A few studies have examined the use of mobile technology in science education and its impact on student learning. Ryu, Han, and Paik () found that smartphones, as supplemental resources to scientific modelling activities, facilitated student collaboration and deepened conceptual discussion. In a quasi‐experiment by Hwang, Wu, and Ke (), elementary school students used interactive concept maps on mobile devices in natural science courses that improved their attitudes towards and achievements in science learning.…”
Section: Introductionmentioning
confidence: 99%
“…The use of the agent-based modeling simulation StarLogo Nova allows for three different representations of the complex system being modeled: first, a visual representation of the interactions of the complex system model; second, mathematical representations of specific outputs over time; and, finally, the blocks-based code representation used to build the model (see Figure 1). It has been shown that multiple representations of the same system can support students' understanding of the system (Jacobson et al, 2011;Ryu et al, 2015;Hmelo-Silver et al, 2017).…”
Section: Complex Systems Modelingmentioning
confidence: 99%
“…Integrating modeling into the elementary science curriculum offers the potential to meet important 21 st century learning goals, including understanding causal relationships in complex systems and infusing computational thinking into disciplinary contexts. These learning objectives have received attention in middle school and high school curricula (Ryu, Han, & Paik, 2015;Vattam et al, 2011), but few examples exist in elementary grades science instruction (Schwarz et al, 2007). Research has revealed that even young students can demonstrate sophisticated reasoning and understandings related to complex causal patterns and features (Gopnik et al, 2004;Grotzer & Basca, 2003;Grotzer & Solis, 2015), and can engage in computer programming activities (Gregg et al, 2012).…”
Section: Objectivesmentioning
confidence: 99%